Optimizing percutaneous reduction and fixation with guidewire modification in pelvic and acetabular fractures: surgical technique and case series - Aiman Mudawi (14150271) (2024)
Background Minimally invasive percutaneous screw fixation for pelvic ring and acetabular fractures has become increasingly popular due to its numerous benefits. However, the precise placement of the screw remains a critical challenge, necessitating a modification of the current techniques. This paper introduces a refined technique employing a modified guidewire to enhance the precision and efficiency of percutaneous fixation in pelvic and acetabular fractures. Methods This study details the surgical techniques implemented for correcting guidewire misdirection in percutaneous screw fixation and includes a retrospective analysis of patients treated with this modified approach over a three-year period. Results In this study, 25 patients with pelvic ring and acetabular fractures underwent percutaneous screw fixation. The cohort, predominantly male (23 out of 25), had an average age of 38 years. The majority of injuries were due to traffic accidents (18 out of 25). Types of injuries included pelvic ring (6 cases), acetabular fractures (8 cases), and combined injuries (11 cases). Various screw types, including antegrade and retrograde anterior column screws, retrograde posterior column screws, and lateral compression screws, were used, tailored to each case. Over an average follow-up of 18 months, there were no additional procedures or complications, such as neurovascular injury or hardware failure, indicating successful outcomes in all cases. Conclusions This study introduces a simple yet effective method to address guidewire misdirection during percutaneous fixation for pelvic and acetabular fractures, offering enhanced precision and potentially better patient outcomes. Further research with a larger patient cohort is required for a more comprehensive understanding of its efficacy compared to traditional methods. Level of evidence IV. Therapeutic Study (Surgical technique and Cases-series). Other Information Published in: European Journal of Orthopaedic Surgery & Traumatology License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s00590-024-03905-x